Adsorption Studies of Pb(II) from Aqueous Solution by Using Activated Carbon of Datura stramonium as An Adsorbent - Mehta, Rishika; daga, Kailash; Gehlot, Poonam (Asian Journal of Chemistry, 2011)
In the present investigation attempts have been made to assess the efficiency of low cost adsorbent material prepared from Datura stramonium for removal of Pb(II) from aqueous solution. Operating variables studied were initial metal ion concentration, pH, temperature and contact time. Equilibrium data fit well with the Langmuir and Freundlich isotherm models. Comprehensive characterization of parameters indicates Datura stramonium to be a good adsorbent for adsorption of Pb(II) to treat wastewaters containing low concentration of the metal.